China-Australia Sustainable Bilateral Economic Relations in the Late 20th - Early 21st Century - Rahman, Md. Sayedur; Shafwat, Maesha (Journal of Business and Management, 2024)
Background: In the New Year 2024, Australia sees the light of hope for the development of relations with China. Relations began to strain when Australia called for an independent investigation into the origin of the coronavirus, and the Chinese government-imposed import bans on almost everything that Australia used to export to China. This ban created a problem between the two countries. The joining of Australia in the QUAD military alliance further strained relations, but the relationship is gradually improving.Objectives: This research aims to examine and assess the issues and opportunities for sustainable bilateral economic relations between China and Australia.Methods: This study uses secondary sources to gather perspectives on China-Australia relations. Although the study is qualitative, a quantitative method is also taken. A survey and data analysis were conducted with 101 participants, including international relations experts, researchers, analysts, government officials, students, businessmen, and civil society members. The data was analyzed using basic quantitative techniques for the trade data.Results: The results show that two-way trade between China and Australia has significantly increased in the last 40 years, making China Australia’s most significant commercial partner. China is Australia’s largest export market, the largest source of tourist spending, and the fastest-growing foreign investment source. Australia exports pearls, precious stones, meat, copper salt, and sulfur dioxide to China while importing electrical and electronic equipment, plastics, iron, and aluminum from China.Conclusion: The study indicates that China and Australia have strong economic interdependency, with China having the largest export markets and tourist destinations. Despite diplomatic issues, their relationship strengthens through trade and economics. In 2014, Australia and China signed an FTA, upgrading their relationship to a comprehensive strategic partnership. Focusing on economics rather than politics could improve trade and economic relations.